Gondolatok az üzletrészek örökléséről - Dúl, János (Debreceni Jogi Műhely, 2014)
The article focuses on the successions of the business shares which are in the Hungarian limited liability companies. There are several changes because of the new Civil Code that affected this area although we have to examine the former regulation because of the period of validity, too. The succession law is the area of the law with whom every people has connection at least once in their life. The number of the legacies grows in which business shares can be founded because more and more people are participating in business societies. The new method of the regulation differs from the previous. The new Hungarian Civil Code (Act V of 2013) consists of not only the “classical” civil law (for example property law, law of contracts) but the family law even the business law. Before this there were two separate laws and because of this situation we have to examine the relation of these laws and their methods of regulations. Afterwards we study the state of the successors in the Hungarian limited liability companies. It diverges from the other companies because the limited liability companies are transitions between general and limited partnerships and joint-stock companies. There were more ideas how to regulate this company; at the end it has differences but not so significant.